Digital Horizons in Teacher Education Development - A. N. Makarenko; L. G. Smyshlyaeva; N. N. Minaev; O. M. Zamyatina (Высшее образование в России)
Modern global challenges reflect the essential features of the Fourth Industrial Revolution and are directly related to the digital transformation of life. The teachers are obliged to master the relevant competences to meet the challenges, as their teaching practices experience significant transformations through the enrichment with the digital component. The current problems in the education system transformation force the researchers to identify the principle transformation characteristics, acquire some new types of pedagogical action and design new teacher education formats. The paper presents the authors’ vision of the new teacher education formats at the target, organizational, activity and technological levels. The authors analyze the regional experience of modernization in the higher pedagogical education on the basis of Federal Standards in Higher Education 3++ at the bachelor and master program levels. The realization experience of the federal project “Modern Digital Educational Environment in the Russian Federation” as a part of the national project “Education” is conceptualized in terms of professional skill enhancement of pedagogical personnel in the Tomsk region. The authors reflect on the development trend of the region research and academic complex in the concept of cooperation and resource consolidation for the “Big University” model. The guidelines for strategic development of Tomsk State Pedagogical University, associated with its digitalization, are outlined. The paper shows the development conditions in the digital transformation of the national system for continuous pedagogical education. The paper materials are based on such research methods as theoretical analysis, expert method, and survey.